SortED a new design tool for 'end-of-life' decision making. (1st June 2007) - Lofthouse, Vicky
'SortED' is an end-of-life decision-making design guide to help companies: (a) quickly identify the implications of the WEEE directive on the products they design, manufacture and import; (b) understand the different end-of-life opportunities available to them; and (c) source practical information to help them implement appropriate strategies as quickly and easily as possible. Developed in recognition of the fact that there were no practical tools to guide the design decision-making process and support the development of financially viable, compliant electrical and electronic products, 'SortED' was created by drawing on the theoretical framework developed during the ESPRC/STI 'Information/Inspiration' project and combining these lessons with practical and focused 'end-of-life' information and examples. This paper reflects on the development of the tool and outlines its key attributes.